2014
DOI: 10.1016/j.juro.2013.10.053
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Mizoribine and a Direct Renin Inhibitor, Aliskiren, on Unilateral Ureteral Obstruction Induced Renal Fibrosis in Rats

Abstract: Aliskiren and mizoribine combination therapy provides increased renal protection against renal fibrosis and unilateral ureteral obstruction induced inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Interestingly, aliskiren significantly inhibited mRNA expression of these proinflammatory cytokines. In one other study (42), aliskiren also reduced MCP-1 mRNA levels in UUO in the obstructed kidney. The effect of aliskiren on cytokine levels, as observed from the present study, indicated its persistently protective action as an anti-inflammatory agent, which improves the inflammatory response and ameliorates the compromised tubular function that is associated with UUO.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, aliskiren significantly inhibited mRNA expression of these proinflammatory cytokines. In one other study (42), aliskiren also reduced MCP-1 mRNA levels in UUO in the obstructed kidney. The effect of aliskiren on cytokine levels, as observed from the present study, indicated its persistently protective action as an anti-inflammatory agent, which improves the inflammatory response and ameliorates the compromised tubular function that is associated with UUO.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, aliskiren has been shown to protect kidneys from acute kidney injuries induced by either contrast (23) or ischemia-reperfusion (17,50) or by chronic kidney diseases (e.g., in diabetic nephropathy) (22,49) as well as by doxorubicin-induced nephrotoxicity (39). Aliskiren alone or in combination with other drugs has also been shown to attenuate renal fibrosis and inflammation induced by ureteral obstruction (8,42,52).…”
mentioning
confidence: 99%
“…Aliskiren is an oral direct renin inhibitor that has been introduced to treat hypertension [ 6 ]. Subsequently, independent of blood pressure control, aliskiren alone or in combination with other drugs has been shown to attenuate renal fibrosis and inflammation induced by unilateral ureteral obstruction (UUO) [ 6 , 13 ]. In a mouse model of UUO, aliskiren decreased the increased levels of inflammatory markers such as renal CD68-positive cells, monocyte chemotactic protein (MCP)-1 and osteopontin mRNA levels in obstructed kidneys [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…TGF‐β1 plays fundamental roles in the following processes: modulation of cell growth, maturation and differentiation, the formation of ECM, homeostasis, plasticity of endothelial cells, immune regulation, apoptosis, angiogenesis and cancer progression (Heldin, Landström, & Moustakas, ; Ikushima & Miyazono, ; Moses & Barcellos‐Hoff, ; Parvani, Taylor, & Schiemann, ; Van Meeteren & Ten Dijke, ). Its reduction in cardiac, renal, hepatic, lung and peritoneal tissues and in diabetic animals treated with the drug is a beneficial effect (Aihara et al, ; Asker et al, ; Bae et al, ; Baracho et al, ; Choi et al, ; Elrashidy, Asker, & Mohamed, ; Gross et al, ; Kavvadas et al, ; Ke et al, ; Kishina et al, ; Lee, Chan, Hsieh, Huang, & Lin, ; Lizakowski et al, ; Sakuraya et al, ; Sun et al, ; Wang et al, ; Weng et al, ; Wu et al, ; Yamada et al, ; Zhao et al, ; Zhou, Liu, Cheung, & Huang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the drug reduced MCP‐1 concentrations in diabetic models (Furukawa et al, ; Kishina et al, ; Sakuraya et al, ; Satoh et al, ). MCP‐1 attracts monocytes to inflammatory sites of the vascular subendothelial space, initiating the migration of these cells into the arterial wall and leading to the formation of foam cells.…”
Section: Discussionmentioning
confidence: 99%